Development of a Novel Tumor-Targeted Vascular Disrupting Agent Activated by Membrane-Type Matrix Metalloproteinases - Atkinson, Jennifer M.; Falconer, Robert A.; Edwards, Dylan R.; Pennington, Caroline J.; Siller, Catherine S.; Shnyder, Steven D.; Bibby, Michael C.; Patterson, Laurence H.; Loadman, Paul M.; Gill, Jason H. (Cancer research (Chicago, Ill.), 2010)
Vascular disrupting agents (VDA) offer a strategy to starve solid tumors of nutrients and oxygen concomitant with tumor shrinkage. Several VDAs have progressed into early clinical trials, but their therapeutic value seems to be compromised by systemic toxicity. In this report, we describe the design and characterization of a novel VDA, ICT2588, that is nontoxic until activated specifically in the tumor by membrane-type 1 matrix metalloproteinase (MT1-MMP). HT1080 cancer cells expressing MT1-MMP were selectively chemosensitive to ICT2588, whereas MCF7 cells that did not express MT1-MMP were nonresponsive. Preferential hydrolysis of ICT2588 to its active metabolite (ICT2552) was observed in tumor homogenates of HT1080 relative to MCF7 homogenates, mouse plasma, and liver homogenate. ICT2588 activation was inhibited by the MMP inhibitor ilomastat. In HT1080 tumor–bearing mice, ICT2588 administration resulted in the formation of the active metabolite, diminution of tumor vasculature, and hemorrhagic necrosis of the tumor. The antitumor activity of ICT2588 was superior to its active metabolite, exhibiting reduced toxicity, improved therapeutic index, enhanced pharmacodynamic effect, and greater efficacy. Coadministration of ICT2588 with doxorubicin resulted in a significant antitumor response (22.6 d growth delay), which was superior to the administration of ICT2588 or doxorubicin as a single agent, including complete tumor regressions. Our findings support the clinical development of ICT2588, which achieves selective VDA targeting based on MT-MMP activation in the tumor microenvironment. Cancer Res; 70(17); 6902–12. ©2010 AACR.